KAJIAN FORMULASI EKSTRAK BUNGA TELANG (Clitoria ternatea) TERHADAP AKTIVITAS ANTIOKSIDAN PADA MINUMAN FUNGSIONAL STUDY OF BUTTERFLY PEA FLOWER (Clitoria ternatea) EXTRACT FORMULATION ON ANTIOXIDANT ACTIVITY IN FUNCTIONAL BEVERAGES - Aan Kurniadi; Dewi Sartika; Novita Herdiana; Susilawati - (Jurusan Teknologi Hasil Pertanian, 2024)
Butterfly pea flower is one of the flowers that can be used as an ingredient in making functional drinks. This research aims to determine the best formulation of a combination of functional drink treatment of butterfly pea flower with the addition of different butterfly pea flower extracts and to determine the antioxidant activity of butterfly pea flower using the DPPH method. This research was structured in a Complete Randomized Block Design (RAKL) with a single factor and 4 replications. The formulation of the telang flower functional drink consists of 6 concentrations, namely 5 mL (P1), 10 mL (P2), 15 mL (P3), 20 mL (P4), 25 mL (P5), 30 mL (P6). The data obtained were analyzed for homogeneity using the Bartlett test and additional data was tested using the Tuckey test, then the data was analyzed for variance (ANARA) to determine the effect between treatments. If there is a real influence, the data is analyzed further with the Honestly Significant Difference Test (BNJ) at the 5% level. The results showed that the best drink formulation was P3 (15 mL of butterfly pea flower extract concentration) which produced a taste with a score of 3.07 (like), color with a score of 3.74 (like), aroma with a score of 3.78 (like), and overall acceptance with a score of 3.63 (likes). The antioxidant activity of the telang flower functional drink ranges between 29.9−42.2% with an IC50 value of 80.14 ppm which is classified as a strong antioxidant.